Nitric Oxide-Induced Calcium Release: Activation of Type 1 Ryanodine Receptor, a Calcium Release Channel, through Non-Enzymatic Post-Translational Modification by Nitric Oxide - Kakizawa, Sho (Frontiers in Endocrinology, 2013)
Nitric oxide (NO) is a typical gaseous messenger involved in a wide range of biological processes. In our classical knowledge, effects of NO are largely achieved by activation of soluble guanylyl cyclase to form cyclic guanosine-3’, 5’-monophosphate. However, emerging evidences have suggested another signaling mechanism mediated by NO: “S-nitrosylation” of target proteins. S-nitrosylation is a covalent addition of an NO group to a cysteine thiol/sulfhydryl (RSH), and categorized into non-enzymatic posttranslational modification of proteins, contrasted to enzymatic posttranslational modification of proteins, such as phosphorylation mediated by various protein kinases. Very recently, we found novel intracellular calcium (Ca2+) mobilizing mechanism, NO-induced Ca2+ release (NICR) in cerebellar Purkinje cells. NICR is mediated by type 1 ryanodine receptor (RyR1), a Ca2+ release channel expressed in endoplasmic-reticular membrane. Furthermore, NICR is indicated to be dependent on S-nitrosylation of RyR1, and involved in synaptic plasticity in the cerebellum. In this review, molecular mechanisms and functional significance of NICR, as well as non-enzymatic posttranslational modification of proteins by gaseous signals, are described.